Midnight rooms : a novel - Coles, Donyae (Amistad, an imprint of HarperCollinsPublishers, 2024)
In 1840 England, Orabella, the orphaned daughter of a white man and a Black woman with no fortune or connections, is married off to the wealthy Elias Blakersby and, whisked away to his family's estate, becomes engulfed by the house's darkness, making her question where her dreams and reality begins.